Creating a Poster with Adobe Mobile Apps. - Harmer, Tony (linkedin.com, 2020)
Learn how to use a host of Adobe mobile apps—including Photoshop Sketch, Adobe Capture, Photoshop Fix, and more—to develop cutting-edge graphic designs.